2016
DOI: 10.1016/j.neuroimage.2015.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Directional patterns of cross frequency phase and amplitude coupling within the resting state mimic patterns of fMRI functional connectivity

Abstract: Functional imaging investigations into the brain's resting state interactions have yielded a wealth of insight into the intrinsic and dynamic neural architecture supporting cognition and behavior. Electrophysiological studies however have highlighted the fact that synchrony across large-scale cortical systems is composed of spontaneous interactions occurring at timescales beyond the traditional resolution of fMRI, a feature that limits the capacity of fMRI to draw inference on the true directional relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 51 publications
4
30
0
1
Order By: Relevance
“…Similarly, dynamic functional connectivity analysis using MEG source imaging also reveals the appearance and disappearance of various sensory or sensory-motor networks over time in the resting brain (de Pasquale et al, 2010; Brookes et al, 2014). Moreover, recent studies have also suggested a possible role of ubiquitous PAC in assisting the resting state network (Wang et al, 2012; Weaver et al, 2016). However, in the present study, PAC phenomenon appeared to be very limited (for the 15 s window length) or almost absent (for the 2 s window length) over multiple time segments across the nodes (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, dynamic functional connectivity analysis using MEG source imaging also reveals the appearance and disappearance of various sensory or sensory-motor networks over time in the resting brain (de Pasquale et al, 2010; Brookes et al, 2014). Moreover, recent studies have also suggested a possible role of ubiquitous PAC in assisting the resting state network (Wang et al, 2012; Weaver et al, 2016). However, in the present study, PAC phenomenon appeared to be very limited (for the 15 s window length) or almost absent (for the 2 s window length) over multiple time segments across the nodes (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an MEG study on PAC during the resting state showed that 41–61% of cortical voxels exhibited significant PAC (Florin and Baillet, 2015). Recent invasive (electrocorticogram [EcoG] and local field potential [LFP]) studies have also suggested ubiquitous PAC phenomenon during the resting state that assists high-frequency communication across remote neuronal assemblies even in the absence of an overt task structure (Wang et al, 2012; Weaver et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging meta-analysis studies that examine the lexicality effect (the difference between words and pseudowords) on adults' brain activation suggest that the familiarity and the lexical status of written stimuli affect the degree to which different reading-related brain regions are involved (Cattinelli et al, 2013; Jobard, Crivello, & Tzourio-Mazoyer, 2003; McNorgan, Chabal, O'Young, Lukic, & Booth, 2015; Mechelli et al, 2005; Protopapas et al, 2016; Pugh et al, 2001, 2010; Taylor et al, 2013). Pseudowords as compared to words show greater activation in regions that are associated with spelling to sound mapping, such as the supramarginal gyrus (SMG) and inferior parietal lobule (IPL) (Graves, Binder, Desai, Conant, & Seidenberg, 2010; Jobard et al, 2003), and phonological processing, such as the superior temporal gyrus (STG) and dorsal inferior frontal gyrus (IFG) (Fiez & Petersen, 1998; Richlan, Kronbichler, & Wimmer, 2011; Turkeltaub, Gareau, Flowers, Zeffiro, & Eden, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that this decrease is consistent with predictions based on other motor learning tasks, suggesting that not only activity patterns but also connectivity patterns of BCI learning and use follow those of motor tasks [54]. However, while pure amplitude-based STWC experienced decreases, nonlinear cross-frequency phase-phase connectivity as assessed by biphase locking (bPLV) [55], [56] remained strikingly consistent throughout the period of task execution, and generally was observed between sites farther apart from each other than those with significant STWC [4]. The heterogeneity of connectivity changes across the brain, across frequency ranges, and between amplitude and phase measures require further investigation.…”
Section: Review Of Current Researchmentioning
confidence: 54%